Selective importance of the rat anterior thalamic nuclei for configural learning involving distal spatial cues. (11th November 2013) - Dumont, Julie R.; Amin, Eman; Aggleton, John P.
Abstract To test potential parallels between hippocampal and anterior thalamic function, rats with anterior thalamic lesions were trained on a series of biconditional learning tasks. The anterior thalamic lesions did not disrupt learning two biconditional associations in operant chambers where a specific auditory stimulus (tone or click) had a differential outcome depending on whether it was paired with a particular visual context (spot or checkered wall‐paper) or a particular thermal context (warm or cool). Likewise, rats with anterior thalamic lesions successfully learnt a biconditional task when they were reinforced for digging in one of two distinct cups (containing either beads or shredded paper), depending on the particular appearance of the local context on which the cup was placed (one of two textured floors). In contrast, the same rats were severely impaired at learning the biconditional rule to select a specific cup when in a particular location within the test room. Place learning was then tested with a series of go/no‐go discriminations. Rats with anterior thalamic nuclei lesions could learn to discriminate between two locations when they were approached from a constant direction. They could not, however, use this acquired location information to solve a subsequent spatial biconditional task where those same places dictated the correct choice of digging cup. Anterior thalamic lesions produced a selective, but severe, biconditional learning deficit when the task incorporated distal spatial cues. This deficit mirrors that seen in rats with hippocampal lesions, so extending potential interdependencies between the two sites.